PERSEPSI RISIKO DAN NIAT PENGGUNAAN ALAT KONTRASEPSI - Putri, Ayu Marlika Leni; Simanjuntak, Megawati (Jurnal Ilmu Keluarga dan Konsumen, 2013)
One of efforts to reduce the birth rate can be conducted by using contraceptive. This study aimed to analyze the relationship among information access, knowledge, perceived risk, and the intention to use contraceptive. The participant of this study were 60 women at reproductive age (15-49 years) who never used contraceptive and selected by purposive sampling method. Data was collected through interview by a questionnaire. The results indicated that the education level and the age of husband and wife had a correlation significantly with the knowledge level of contraceptive use. In addition, the knowledge level about contraceptive use also related to the number source and the trusted source of information. The results also revealed that there was not variable correlated with perceived risk. Perceived risk of between hormonal and nonhormonal contraceptives had significant difference on functional, physical, financial, social, time, and opportunity cost dimention but not at perceived risk in several. Meanwhile, intention to use had positive correlation with husband of wife’s education level.